1985
DOI: 10.2151/jmsj1965.63.5_829
|View full text |Cite
|
Sign up to set email alerts
|

The 10-20 Day Tropical-Midlatitude Interactions during the Winter Monsoon Season

Abstract: The lower-frequency variations in the winter monsoon system have been examined using a l0-day low-pass filter. Results indicate that the lower tropospheric north-south thermal gradient over eastern Asia, the Siberian high pressure system, and the eastern Asia subtropical jet stream varied coherently with a time scale of 10-20 days. Composite study reveals that the 200-mb streamfunction variations on the 10-20 day time scale are longsynoptic-scale disturbances propagating slowly eastward. The cyclonic disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The variation of EAWM is also well linked to the ISO through the tropical-midlatitude interaction (Pan and Zhou 1985;Hsu et al1990;Compo et al 1999;Kiladis and Weickmann 1992;Meehl et al 1996;Jeong et al 2005;Pan and Li 2007). For example, the temporal variation of surface temperature anomalies at Guangzhou in southern China shows a clear 30-60-day oscillation (Li 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The variation of EAWM is also well linked to the ISO through the tropical-midlatitude interaction (Pan and Zhou 1985;Hsu et al1990;Compo et al 1999;Kiladis and Weickmann 1992;Meehl et al 1996;Jeong et al 2005;Pan and Li 2007). For example, the temporal variation of surface temperature anomalies at Guangzhou in southern China shows a clear 30-60-day oscillation (Li 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been made to understand the variability of the EA winter climate by meteorologists (Lau and Li 1984;Zhang et al 1997a;Gong et al 2001;Wu and Wang 2002;Jhun and Lee 2004;Takaya and Nakamura 2005). Fluctuations from the synoptic to intraseasonal scale have been identified (Murakami 1979;Pan and Zhou 1985;Takaya and Nakamura 2005). The interannual to interdecadal variability of the EA circulation was also examined in some observational studies (see, e.g., Zhang et al 1997a;Chen et al 2000;Zhu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study by Pan and Zhou (1985) has demonstrated the importance of the upper tropospheric long-synoptic scale waves in the modulation of the cold air outbreak over the winter monsoon domain. Results of this study indicate that these longsynoptic scale waves are part of a hemispheric wavetrain that propagates slowly eastward.…”
Section: Introductionmentioning
confidence: 98%
“…Observational studies have demonstrated that the winter monsoon circulation undergoes strong variations on the medium-range time scale (Murakami and Unninayer, 1977;Murakami, 1981;Murakami and Sumi, 1981;Lau and Lau, 1984;Pan and Zhou, 1985). Composites of the winter monsoon circulation using the peaks in the low pass filtered surge index (Ramage,1971-;Pan and Zhou, 1985, hereafter referred to as PZ) as reference dates revealed that the lower tropospheric thermal anomalies (represented by the 500mb-1000mb thickness field) and the sea-level pressure anomalies propagate southeastward from northern Eurasia toward the subtropical western Pacific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation